(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Companies have long engaged in head-to-head competition in search of sustained, profitable growth. They have fought for competitive advantage, battled over market share, and struggled for differentiation. Yet in todays overcrowded industries, competing head-on results in nothing but a bloody red ocean of rivals fighting over a shrinking profit pool. Tomorrows leading companies will succeed not by battling competitors, but by creating blue oceans of uncontested market space ripe for growth. Such strategic moves termed value innovation create powerful leaps in value for both the firm and its buyers rendering rivals obsolete and unleashing new demand.